2019
DOI: 10.2196/11266
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as a Therapy Adjunct for Fear of Movement in Veterans With Chronic Pain: Single-Arm Feasibility Study

Abstract: BackgroundVirtual reality (VR) has demonstrated efficacy for distraction from pain-related thoughts and exposure to feared movements. Little empirical VR research has focused on chronic pain management.ObjectiveThe purpose of this study was to examine the feasibility of VR as an adjunctive intervention for Veterans with chronic pain. We designed a hierarchy ranging from low-intensity pain distraction to high-intensity movement-based exposure for this purpose. VR apps were mapped onto the hierarchy.MethodsSixte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 50 publications
(90 reference statements)
2
34
0
Order By: Relevance
“…We feel this is a sufficient subject pool from which to enroll the target sample size of 10 patients (16% of the patients admitted over the 18-month enrollment period). We have found that the technology is motivating for patients, which will help retention [42].…”
Section: Recruitmentmentioning
confidence: 96%
See 1 more Smart Citation
“…We feel this is a sufficient subject pool from which to enroll the target sample size of 10 patients (16% of the patients admitted over the 18-month enrollment period). We have found that the technology is motivating for patients, which will help retention [42].…”
Section: Recruitmentmentioning
confidence: 96%
“…In a pilot study [41,42] in the James A Haley Veterans' Hospital (JAHVH) inpatient Chronic Pain Rehabilitation Program, our team found evidence for the feasibility of immersive VR within the chronic pain population as well as a decrease in fear of movement, pain interference with mobility, pain intensity, and pain catastrophizing. Veteran attendance (91%) and completion of attended 20-minute VR sessions was high (97%).…”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Fear of movement can restrict people living with chronic pain ( Lamé et al, 2005 ; Tufnell, 2017 ; Fowler et al, 2019 ; Simons et al, 2020 ). The somatic processes of attention to the environment in exteroception, and registering movement, balance and position in proprioception allow the person living with pain to explore movement in space, especially with regard to fears of movement.…”
Section: Discussionmentioning
confidence: 99%
“…Yelvar et al [ 53 ] reported that passively viewing VR walking scenes during physical therapy may improve pain-related outcomes in individuals with cLBP. Additionally, Fowler et al [ 54 ] studied the use of VR to gradually expose veterans with chronic pain to progressively more involved movements. They found that gradual VR exposure was feasible but also reported that users rated the activities, designed to progressively deliver more exposure, with similar intensity ratings [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fowler et al [ 54 ] studied the use of VR to gradually expose veterans with chronic pain to progressively more involved movements. They found that gradual VR exposure was feasible but also reported that users rated the activities, designed to progressively deliver more exposure, with similar intensity ratings [ 54 ]. Although these applications are useful to train specific movement tasks and support that VR may be an acceptable way to address chronic pain, the VR application described in this study is the first app, to our knowledge, designed specifically to apply VR GEXP in an interactive walking protocol for individuals with cLBP.…”
Section: Discussionmentioning
confidence: 99%